Similar maximal oxygen uptake assessment from a step cycling incremental test and verification tests on the same or different day - Possamai, L. T.; de Souza Campos, F.; do Nascimento Salvador, P. C.; Alves de Aguiar, R.; Antonacci Guglielmo, L. G.; Dantas de Lucas, R.; Caputo, F.; Turnes, T. (Applied Physiology, Nutrition, and Metabolism, 2020)
The present study aimed to compare maximal oxygen uptake of a step incremental test with time to exhaustion verification tests (TLIM) performed on the same or different day. Nineteen recreationally trained cyclists (age: 23 ± 2.7 years; maximal oxygen uptake: 48.0 ± 5.8 mL/kg·min) performed 3 maximal tests as follows: (i) same day: an incremental test with 3-min stages followed by a TLIM at 100% of peak power output of the incremental test (TLIM-SAME) interspaced by 15 min; and (ii) different day: a TLIM at 100% of peak power output of the incremental test (TLIM-DIFF). The maximal oxygen uptake was determined for the 3 tests. The maximal oxygen uptake was not different among the tests (incremental: 3.83 ± 0.41; TLIM-SAME: 3.72 ± 0.42; TLIM-DIFF: 3.75 ± 0.41 L·min-1; P = 0.951). Seven subjects presented a variability greater than ±3% in both verification tests compared with the incremental test. The same-day verification test decreased the exercise tolerance (240 ± 38 vs. 310 ± 36 s) compared with TLIM-DIFF (P < 0.05). In conclusion, the incremental protocol is capable of measuring maximal oxygen uptake because similar values were observed in comparison with verification tests. Although the need for the verification phase is questionable, the additional tests are useful to evaluate individual variability. Novelty Step incremental test is capable of measuring maximal oxygen uptake with similar values during TLIM on the same or different day. Although the necessity of the verification phase is questionable, it can allow the determination of variability in maximal oxygen uptake.